Early Reputation Management: Three-Year-Old Children Are More Generous Following Exposure to Eyes - Kelsey, Caroline; Grossmann, Tobias; Vaish, Amrisha (Frontiers in Psychology, 2018)
To enhance their reputations, adults and even 5-year-old children behave more prosocially when being observed by others. However, it remains unknown whether children younger than five also manage their reputations. One established paradigm for assessing reputation management is the ‘watching eyes paradigm,’ in which adults have been found to be more prosocial in the presence of eyes versus control images. However, the robustness of this effect in adults has recently been called into question, and it has never been demonstrated in children. In Study 1, we used a method similar to that used in prior work: 3- and 5-year-old children took part in a prosocial task while in the presence of an image of eyes or flowers but without explicit mention or reference to the image. With this method, children did not show the watching eyes effect. In Study 2, 3-year-old children were tested with a modified watching eyes paradigm, wherein they first explicitly interacted either with images of eyes or with cloth flowers, and they then engaged in a prosocial task. With this modified watching eyes paradigm, 3-year-olds showed the predicted effect: They were more prosocial following exposure to eyes than flowers. These results offer potential insight into the mixed findings across the adult literature, such that the manner of exposure, and specifically how explicit the exposure is, may influence the watching eyes effect. Finally, no study to date has examined whether cues of human presence other than the eyes also influence prosociality. We found that children in the Mouth condition were prosocial at an intermediate level between the Eyes and Flowers conditions. Overall, the findings point to the remarkably early emergence of reputation management in human ontogeny.